PENGENDALIAN WAKTU DAN ANGGARAN BIAYA PADA PROYEK PEMBANGUNAN BANGUNAN PENGENDALI SEDIMEN BATANG KURANJI DAN ANAK SUNGAINYA (SEGMEN HULU) KOTA PADANG DENGAN METODE EARNED VALUE - Nasrul Nasrul; Sintia Sintia (Ensiklopedia of Journal, 2020)
The main resources limited to the implementation stage of a construction project are cost, quality and time. Planning, schedule and control are important steps to take in order for the objectives of the implementation of this project with limited resources to be achieved. The "Eaned Value" method is a control method used for project performance during a reporting period and provides information on the cost prediction required and the time for completion of the entire work based on performance indicators when reporting. The type of research used in this study is qualitative, qualitative research is research on research that is descriptive and uses analysis. Process and meaning are more prominent in qualitative research. The foundation of the theory is used as a guide for research according to the facts. During the review period from the beginning to the last week there is a difference from the calculation of BCWS and BCWP namely the addition and reduction of costs at certain points and in the calculation there is a faster volume of work completed and some who experience delays from the plan and benefit and losses from the peoggres-proggres. Based on the results of the analysis using Earned Value on the project Construction of Sediment Control Building Batang Kuranji And Its Tributaries (Upstream Segment) Padang City the time needed to complete this project 184 calendar days with a budget plan costing Rp 4,499,420,674.00 Last week in the project's work in a timely and targeted way with no reduction or addition of days and costs in its implementation , so that the workmanship can get 100% good workmanship on this project.